KEKUTAN HUKUM AKTA PERJANJIAN PENGIKATAN JUAL BELI TANAH (STUDI DI DESA BABAKAN KECAMATAN SANDUBAYA KOTA MATARAM) - GEDE TUSAN ARDIKA; RAMLI RAMLI (GANEC SWARA, 2019)
This study aims to determine: the form of legal protection for the parties due to the law from the cancellation of the land purchase agreement and the factors underlying the cancellation of the binding deed of sale and purchase of land in Babakan Village, Sandtubaya District, Mataramt City.     This type of research is normative-empirical research, using the statute approach, conceptual approach, case analysis approach (case approach) and fact approach. The sources of legal material used are in the form of primary legal materials, secondary legal materials and tertiary legal materials. Field data collection using interview techniques, then analyzed qualitatively.     From the results of the study, it can be concluded that 1) The legal strength of the sale and purchase rights agreement on land rights made by a Notary in the implementation of the Deed of Sale and Purchase is very strong. Because it is an authentic deed, 2) Legal consequences arises from the cancellation of the Land Purchase Sale deed: (a) The parties may be liable to a fine which has been agreed upon from the amount that must be paid by the buyer to the seller or buyer, for each day of delay. These fines must be paid instantly and at once, (b) The agreement ends and insofar as both parties need to break away from what is stipulated in Article 1266 and Article 1267 of the Civil Code, and the Seller Party is obliged to return the money paid by the Party The buyer after deducting a few percent from the selling price of the land and building in lieu of the costs incurred by the Selling Party plus the fine that must be paid by the Purchaser to the Seller